Scores for Effective Forest Conservation: A Village-to- Village Approach - Pokharel, RK; Larsen, HO (Banko Janakari, 2009)
Community forestry in Nepal strives for forest conservation and sustainable forest management. Evaluating progress towards this end requires periodic measurements, and currently there are no standard tools for undertaking evaluations in a participatory way. The purpose of this paper is to suggest a standardized way for measuring effective forest conservation through the use of locally set scores. A village-to-village approach was used to assign scores on criteria and indicators developed earlier for forest conservation. A total of eight small meetings with forest users were conducted to elicit their perspectives and quantify their progress towards conservation by means of scores. For the 14 criteria specified, local forest users assigned higher scores to four criteria: two for social and one each for socio-economic and environmental spheres. This paper argues that a score of 59 or above is an effective cut off for determining "effective" forest conservation. Keywords: Community forest, criteria, forest management, indicator, village doi: 10.3126/banko.v19i1.2177 Banko Janakari, Vol. 19, No. 1, 11-15